Climate change in public health and medical curricula in Australia and New Zealand: a mixed methods study of educator perceptions of barriers and areas for further action. Issue 7 (3rd July 2022) - Lal, Aparna; Walsh, Erin I.; Wetherell, Alice; Slimings, Claudia
Abstract: The importance of a safe climate for human health is recognised by healthcare professionals, who need to be equipped to deliver environmentally sustainable healthcare and promote the health of natural systems on which we depend. The inclusion of climate-health in Australian and New Zealand accredited master-level public health training and medical programs is unclear. Educators identified by their coordination, convenorship, or delivery into programs of public health and medicine at universities in Australia and New Zealand were invited to participate in a cross-sectional, exploratory mixed methods study to examine the design and delivery of climate change content in the curricula, and the barriers and opportunities for better integration. Quantitative surveys were analysed using descriptive statistics and qualitative interview content was analysed via a modified grounded theory approach. The quantitative survey had 43.7% (21/48) response rate, with 10 survey respondents completing qualitative interviews. Qualitative interviews highlighted the minimal role of Indigenous-led content in this field, the barriers of time and resources to develop a coherent curriculum and the role of high-level champions to drive the inclusion of climate change and planetary health. Building pedagogical leadership in in the area of climate change and health teaching at universities through stronger partnerships with policymakers, community stakeholders and advocacy organisations will be important for future health workforce training amid increasing climate risks. Supplemental data for this article is available online at https://doi.org/10.1080/13504622.2022.2036325 .